Shifting to Sustainable Management by implementing Blockchain technology in agri-food supply chains: hype or hope for SMEs - Duarte de Almeida, I.; Cardoso-Grilo T; Harms, J. (Proceedings of 28th EurOMA Conference, 2021)
Sustainability awareness and the food industry's challenges force agri-food companies to implement sustainable actions. Agri-food supply chain networks complexity/fragmentation are barriers to detect suppliers' unsustainable practices. Implementing traceability mechanisms allow identifying unsustainable links within supply chains, and Blockchain-technology (BCT) has been advocated as a truthful option. Through a case study, BCT drivers and challenges were addressed to evaluate BCT implementation success in a German organic food SME. Our findings show that SMEs faces two major decisions: how to facilitate network collaboration, and which data to capture in BCT. Additional challenges include data protection, data-input verification, interoperability, and BCT workers' skills. (https://event.euroma2021.exordo.com/presentation/544/shifting-to-sustainable-management-by-implementing-blockchain-technology-in-the-food-supply-chain-hype-or-hope-for-smes)